A new simulation model for hydrodynamic behavior of rigid body in narrow space. (15th June 2019) - Zhang, Lei; Lin, Shiyao; Wang, Chizhong; Xie, De; Sun, Jianglong
Abstract: Hydrodynamic motion of rigid body in narrow space is a common phenomenon in nature and ocean engineering application. In this paper, a new simulation model based on Fluent is proposed to solve this kind of fluid-structure interaction problem in which added-mass effect is strong. In this new model, hydrodynamic force is decomposed, and a new six-degree-of-freedom rigid-body motion equation is formed with added mass force being added to both sides of the motion equation used by 6DOF solver in Fluent. First of all, numerical results of free-floating rigid body in open domain by 6DOF solver and experimental data of free-falling sphere in still water are presented for the validation of this new simulation model. Then, the scope of this model is studied. It is found that 6DOF solver in Fluent cannot solve the hydrodynamic motion of rigid body if added-mass effect is strong, while this new model is apt for this kind of problem and has good convergent characteristics. Finally, hydrodynamic behavior of rigid body in a changing domain is simulated by the new model. Acceleration and spatial displacement curves are obtained, and details of flow at some key moments are presented and analyzed. Highlights: A new simulation model improves Fluent in solving hydrodynamic behavior of rigid body with strong added-mass effect. The scope of the new simulation model is introduced by comparative analyses with 6DOF solver in Fluent. Added mass of rigid body in the changing domain is estimated. The hydrodynamic motion of rigid body in the changing domain is analyzed.